(untitled) (Experimental biology, 2018)
The wheat DELLA proteins encoded by the plant height reducing (Rht-1) genes. Wheat DELLA genes have three homologous loci (Rht-A1, Rht-B1, and Rht-D1) in the 4A, 4B, and 4D chromosomes, respectively. Despite the importance of the Rht-1 proteins, little biochemical analyses have been reported, mainly due to difficulties with purification of sufficient quality of protein and absence specific antibodies to this protein. Here, we isolated the Rht-D1a cDNA gene encoding the wheat Rht-D1a using the reverse transcription - polymerase chain reaction (RT-PCR). Rht-D1a with a 6xHis end was functionally expressed in E. coli and purified by nickel affinity chromatography. Using MALDI-TOF mass spectrometry, a complete coincidence of the amino acid sequence of the recombinant protein with the primary structure of the DELLA protein Triticum aestivum was established. It was revealed that the product of gene expression is a globular protein with a mass of 65.3 kDa, consisting of 623 amino acids (pI 4.99). Purified Rht-D1a was used as an immunogen to generate rabbit polyclonal anti-Rht-D1a antibodies. Our purified preparation of the wheat Rht-D1a and antibodies generated against the recombinant Rht-D1a is suitable for further structural and functional studies that will contribute to precise understanding of the plant regulation mechanism through Rht-D1a proteins. Key words: Triticum aestivum, Rht-D1a, DELLA-protein, aleurone, expression.